La coanalyse entre pairs en formation initiale des enseignants : une opportunité d'apprentissages professionnels - Élisabeth Magendie; Magali Boizmault; Florence Darnis (Université de Provence, 2021)
The purpose of this exploratory study is to highlight, in the context of initial teacher training, the possible transformations brought by a training environment based on a situation of peer co-analysis, and thus to find out whether it can offer opportunities for professional learning. The approach seeks to identify the traces of re-elaboration of the experience that emerge from the exchanges carried out by the students during the time of co-analysis. It then consists of identifying the traces of learning in the teaching activity of the trainees. Two students in their second year of the Master's degree in teaching and training, who had previously been trained in the role of tutor (observer/analyst), took part in the study. The results show that the situation allows them, under certain conditions, to appropriate and consolidate professional knowledge. In particular, the co-constructed proposals should relate to the students' concerns, respond to problems raised by the tutor, and be formulated by the tutor. The instructor's assistance also seems necessary. Impacts on training are then envisaged.